2017
DOI: 10.5539/jel.v7n1p116
|View full text |Cite
|
Sign up to set email alerts
|

Should We Flip the Social Studies Classrooms? The Opinions of Social Studies Teacher Candidates on Flipped Classroom

Abstract: The technology revolution continues to profoundly influence the educational process. Thus, the traditional teaching process is changing and education which is individualized with technology supported teaching processes comes to the forefront. One of the concrete indicators is the flipped classroom model. The purpose of this study is to determine the opinions of the teacher candidates who continue the undergraduate program of social studies education towards the flipped classroom model and its usability in soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 20 publications
2
5
0
4
Order By: Relevance
“…The majority of the students complained about the length of the videos. This result is in accordance with the results obtained by Kettle (2013), Schultz, Duffield, Rasmussen andWageman (2014), Zainuddin and Attaran (2016), Erdogan and Akbaba (2018). Results showed that the instructional videos were too long.…”
Section: Discussionsupporting
confidence: 92%
“…The majority of the students complained about the length of the videos. This result is in accordance with the results obtained by Kettle (2013), Schultz, Duffield, Rasmussen andWageman (2014), Zainuddin and Attaran (2016), Erdogan and Akbaba (2018). Results showed that the instructional videos were too long.…”
Section: Discussionsupporting
confidence: 92%
“…In addition, the FCM holds a considerably noteworthy significance for EFL students (Moraros et al, 2015). As per the findings of this content analysis, it is evident that the number of publications related to the FCM in education have dramatically increased from the years between 2011 to 2020 (21 st April) which clearly demonstrates the interest of teachers, students and researchers in the implementation of the respective model (Rachmawati et al, 2019;Erdogan & Akbaba, 2018). Revealing the importance of Flipped Learning in Education, the findings of this study spotlights the fact that this model has found to be rather more effective in the teaching of subjects that require cognitive skills like social studies, medicine, and computer science, moreover it was found that FLM was mostly practiced in the United States, Europe and Asia.…”
Section: Conclusion Recommendations and Limitationssupporting
confidence: 53%
“…This is in line with the study of Al-Shabibi and Al-Ayasra (2019) who found that FCM has lesser or limited implications in "applied science such as mathematics and science" (p. 105). Erdogan and Akbaba (2018) conducted a study regarding flipped classroom the aim of which was to explore the opinions of teachers on flipped classroom in Social Studies, and their phenomenological study, laid out the fact that integrating FLM into Social Sciences solves problems like time management and absences (Erdogan & Akbaba, 2019).…”
Section: Languagesmentioning
confidence: 99%
“…Bu açıdan bu araştırmanın amacı; ters yüz edilmiş sınıf modelinin, öğrencilerin 6. sınıf "Sosyal Bilgiler" dersi "İpek Yolunda Türkler" ünitesindeki akademik başarılarında süreç içerisinde nasıl bir değişiklik oluşturduğunu ortaya çıkarmaktır. Ulusal literatüre ters yüz edilmiş sınıf modeliyle gerçekleştirilen araştırmalar açısından bakıldığında, ortaokul düzeyinden lisans eğitimi sürecine değin araştırmalar bulunmasına rağmen bunların sayısının oldukça az olduğuna ulaşılmıştır (Gençer, 2015;Turan ve Göktaş;Göğebakan-Yıldız, Kıyıcı ve Altıntaş, 2016;Kocabatmaz, 2016;Cukurbasi ve Kiyici, 2017;Akgün ve Atıcı, 2017;Köse ve Acar, 2017;Çakır ve Yaman, 2017;Erdogan ve Akbaba, 2018). Uluslararası literatürde ise ters yüz edilmiş sınıf modeliyle ilgili daha fazla araştırma gerçekleştirildiği görülmektedir (Snyder, Paska ve Besozzi, 2014;Hultén ve Larsson, 2016;Unruh, Peters ve Willis, 2016;Zainuddin ve Attaran, 2016;Aidinopoulou ve Sampson, 2017;Lo ve Hew, 2017;Latif, Matzin, Jawawi, Mahadi, Jaidin, Mundia ve Shahrill, 2017;Winter, 2018).…”
Section: Ters Yüz Edilmiş Sınıf Modeliunclassified